The Diagnostic Utility of Ultrasonography, CT and PET/CT for the Preoperative Evaluation of Cervical Lymph Node Metastasis in Papillary Thyroid Cancer Patients - Youngsang Kim; Taehyun Lee; Donghee Park (대한영상의학회지, 2016)
Purpose To compare the diagnostic utility of ultrasonography (US), CT and positron emission tomography/CT (PET/CT) in the preoperative evaluation of cervical lymph node metastasis in patients with papillary thyroid carcinoma.